Lung/Polmone (C34.9) - Management considerations for acute limb ischaemia complicating invasive squamous cell lung cancer - Lee, Regent (European Journal of Oncology and Environmental Health, 2014)
Management of acute limb ischaemia (ALI) in patients with significant, but not yet terminal, medical co-morbidities can be challenging. This case highlights the management considerations for a patient with a locally invasive squamous cell lung carcinoma, who developed unilateral ALI while receiving in-hospital treatment for pneumonia. There were limited options for pain relief due to the inherent risk of respiratory complications. Treatment option for the ALI was likewise limited. Surgical thrombo-embolectomy was successfully performed under local anaesthesia. This offered full resolution of symptoms and allowed the patient to have one good night’s sleep at last.